1975
DOI: 10.1021/bi00691a012
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli stringent factor binds to ribosomes at a site different from that of elongation factor Tu or G

Abstract: The binding of Escherichia coli stringent factor to ribosomes has been studied; the reaction depends on 50S and 30S ribosomal subunits and poly(U) as messenger RNA. The ribosome-stringent factor complex is formed at 5-10 mM magnesium acetate; NH4 ions are inhibitory. Binding of the stringent factor to the 70S-mRNA complex is not stimulated by uncharged tRNA. The ribosomal binding site(s) for the stringent factor does not overlap with the one known for the elongation factor Tu (EF-Tu) or G (EF-G). Ribosomes car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

1975
1975
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 37 publications
0
17
1
Order By: Relevance
“…SpoT, together with RelA, regulates ppGpp accumulation in response to cell stress and nutrient deprivation (7). Both SpoT and RelA are thought to associate with and are functionally supported by the ribosome (19,39,42). Recently, CgtA was shown to promote SpoT-dependent activities on the ribosome (24).…”
Section: Discussionmentioning
confidence: 99%
“…SpoT, together with RelA, regulates ppGpp accumulation in response to cell stress and nutrient deprivation (7). Both SpoT and RelA are thought to associate with and are functionally supported by the ribosome (19,39,42). Recently, CgtA was shown to promote SpoT-dependent activities on the ribosome (24).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in good agreement with previous experiments in which it was shown that the two acidic proteins L7/L12 from the large ribosomal subunit are not required for the pyrophosphoryl transfer reaction [ 17,18], whereas they are for EF-Tu and EF-G functions [1,2]. The possibility that transferase and elongation factors do not bind to the same but rather to different ribosomes is unlikely, because ribosomes precharged with EF-Tu or EF-G were inactive in the pyrophosphoryl transferase-dependent formation of pppGpp and ppGpp but active in binding the transferase [16]. The inhibition of the synthesis of guanosine Volume 55, number 1 FEBS LETTERS July 1975 Binding of the [3 HI pyrophosphoryl transferase to the 70S-poly U complex and isolation of the complexed ribosomes were carried out as outlined in the legend to table 3.…”
Section: Resultsmentioning
confidence: 99%
“…polyphosphates was due to the blocking of the acceptor site of the peptidyltransferase center by the elongation factor and/or aminoacyl-tRNA [ 16].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SF does not compete either with the binding of elongation factors or with their function (23). Therefore, it is an obvious assumption that SF can remain bound to the 70S ribosome during protein synthesis.…”
Section: Discussionmentioning
confidence: 99%